Honing self-awareness of faculty and future business leaders : emotions connected with teaching and learning - Kumar, Payal; Culham, Tom Elwood; Major, Richard J.; Peregoy, Richard (Emerald Publishing Limited, 2023)
Addressing the topic of emotions in the classroom is largely done by education and psychology scholars, not those in management fields. Occupying this gap, the chapter authors emphasize self-awareness and management of emotions to strengthen student engagement, well-being and performance in complex and ambiguous societal and economic VUCA environments. Honing Self-Awareness of Faculty and Future Business Leaders prepares 21st century managers and teachers in business schools and other higher education institutions - not only be able to deal with emotions that arise in the classroom, but to emanate heightened emotional intelligence themselves - aiding personal and interpersonal development and forming the foundation of leader self-awareness.